FRI0274 HISTORY OF BIOLOGICS AND FEMALE GENDER ARE LINKED TO GOLIMUMAB DISCONTINUATION IN AXIAL SPONDYLOARTHRITIS: A SUB-ANALYSIS OF THE GO-PRACTICE STUDY. (2nd June 2020) - Bertin, P.; Goupille, P.; Tubach, F.; Lespessailles, E.; Harid, N.; Sequeira, S.; Fayette, J. M.; Fautrel, B.; Flipo, R. M.
Abstract : Background: Golimumab (GLM ) is the latest anti-TNFα to be indicated for treating rheumatoid arthritis (RA ), psoriatic arthritis (PsA ) and axial spondyloarthritis (axSpA ). The GO-PRACTICE study was performed in France at the request of the French Health Authorities, for the reevaluation of GLM in real-life. Objectives: The primary objective was to estimate GLM persistence at 2 years from initial prescription. This abstract focuses on a post-hoc analysis of the factors linked to GLM discontinuation in axSpA patients. Methods: Observational, prospective, multicenter study, that consecutively recruited adult patients with RA, PsA and axSpA who were newly prescribed GLM. Patients were followed-up for 2 years and outcomes data were collected at baseline (BL ), 1 and 2 years. Patients' sociodemographic characteristics, disease history, comorbidities and treatment history were also collected at BL. Persistence was estimated with the Kaplan-Meier method. Cox proportional hazard models were used to assess factors associated with persistence. Selected BL characteristics were studied in univariate models, where those associated with p -value <0.20 were included in multivariate analysis. Significance level was set at p <0.05. Results: 478 patients with axSpA were included from Jan 2015 to Mar 2016. Mean age was 43 years and 55% were female; 61% of patients were biologic-naïve (BN, n=291) and 39% (n=187) were biologic-pretreated (BP). Median time-elapsed in years since axSpA diagnosis was 1.7 (range 0–45.1) and 6.9 (range 0.2–51.8) in BN and BP patients, respectively ( P <0.001); 97% patients were prescribed 50 mg GLM monthly and co-treatments included DMARD (34%), corticosteroids (17%) and NSAIDs/analgesics (90%). Cumulative persistence probability of GLM at 2-years was 52.6% (Fig 1 ). Table 1 details the binary variables associated with GLM discontinuation at p <0.20. Among continuous variables, BL CRP level was associated with p <0.20. A multivariate analysis of these factors revealed that being female (HR 1.92, 95%CI 1.43–2.56, P <0.001) and being BP (HR 1.45, 95%CI (1.11–1.90), P =0.007) were risk factors for GLM discontinuation (Table 1 ). Conclusion: 2-year GLM persistence in axSpA patients was 52.6%. Females and those who were biologics-pretreated were at greater risk for discontinuing GLM before 2 years. Disclosure of Interests: Philippe Bertin Consultant of: MSD France, Philippe Goupille Grant/research support from: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Consultant of: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Speakers bureau: AbbVie, Amgen, Biogen, BMS, Celgene, Chugai, Lilly, Janssen, Medac, MSD France, Nordic Pharma, Novartis, Pfizer, Sanofi and UCB, Florence Tubach Grant/research support from: Florence TUBACH is head of the Centre de Pharmacoépidémiologie (Cephepi) of the Assistance Publique – Hôpitaux de Paris and of the Clinical Research Unit of Pitié-Salpêtrière hospital, both these structures have received research funding, grants and fees for consultant activities from a large number of pharmaceutical companies, that have contributed indiscriminately to the salaries of its employees. Florence Tubach didn't receive any personal remuneration from these companies., Eric Lespessailles Consultant of: Amgen, Celgene, Lilly, MSD France, Novartis, UCB, Speakers bureau: Amgen, Celgene, Lilly, MSD France, Novartis, UCB, Naoual HARID Employee of: MSD France, Saannya Sequeira Consultant of: MSD France, Jean-Marie Fayette Consultant of: MSD France, Bruno Fautrel Grant/research support from: AbbVie, Lilly, MSD, Pfizer, Consultant of: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celgene, Lilly, Janssen, Medac MSD France, Nordic Pharma, Novartis, Pfizer, Roche, Sanofi Aventis, SOBI and UCB, René-Marc Flipo Consultant of: Johnson and Johnson, MSD France, Novartis, Sanofi, Speakers bureau: Johnson and Johnson, MSD France, Novartis, Sanofi